EFFECT OF ADDING Y2O3 AND ZRO2 TO ODS STEEL ON CORROSION IN A PB ENVIRONMENT FOR GENERATION IV REACTORS - Setyo Hadi, Dhimas
Nuclear energy is known as an environmentally friendly energy source with low emissions compared to other energy. Generation IV nuclear reactors. One type of reactor is the Lead-Cooled Fast Reactor which uses lead as a coolant. The use of lead offers several advantages, but there is the problem of corrosion at high temperatures which can damage reactor components. To overcome this problem, coating materials such as ODSS steel (Oxide Dispersion Strengthened steel) are used because of their resistance to corrosion. This research examines the effect of adding two oxides to ODSS material on corrosion in a lead environment. The research was carried out in two stages: material synthesis and corrosion tests. Material synthesis using the powder metallurgy method. Then the synthesis results will go through material characterization consisting of Optical Microscope, SEMEDX, and Hardness Test. Optical Microscope shows that each sample has a ferritic grain structure, reinforced by SEM-EDX which confirms the presence of porous grains due to the powder metallurgy process. The EDX results showed a homogeneous composition, indicating an ideal synthesis process. Grain size was found to influence the structural density of the material and its mechanical properties, confirmed by the Vickers Hardness Test which shows an inverse ratio between grain size and material hardness. Corrosion tests were carried out in a static Pb environment at a temperature of 550°C for 75 hours. The samples tested were then analyzed using SEM-EDX. The results show the formation of an oxide layer on the sample surface with different characteristics. Analysis shows that the addition of two oxides to ODS steel influences the formation of an oxide layer, which plays an important role in improving the corrosion resistance of the material.